2008
DOI: 10.1021/es800387p
|View full text |Cite
|
Sign up to set email alerts
|

Transport Characteristics of Nanoscale Functional Zerovalent Iron/Silica Composites for in Situ Remediation of Trichloroethylene

Abstract: Effective in situ remediation of groundwater requires the successful delivery of reactive iron particles through soil. In this paper we report the transport characteristics of nanoscale zerovalent iron entrapped in porous silica particles and prepared through an aerosol-assisted process. The entrapment of iron nanoparticles into the silica matrix prevents their aggregation while maintaining the particles' reactivity. Furthermore, the silica particles are functionalized with alkyl groups and are extremely effic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
100
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 170 publications
(102 citation statements)
references
References 35 publications
1
100
1
Order By: Relevance
“…Nanoparticles must be able to flow deep into the reservoir to assist in oil displacement, studies have shown that some challenges are encountered in the flow of nanoparticles in porous media [93,94]. Therefore, the need to understand the mechanism affecting the flow of nanoparticles in porous media is of importance.…”
Section: Nanoparticle Flow Behaviour In Porous Mediamentioning
confidence: 99%
“…Nanoparticles must be able to flow deep into the reservoir to assist in oil displacement, studies have shown that some challenges are encountered in the flow of nanoparticles in porous media [93,94]. Therefore, the need to understand the mechanism affecting the flow of nanoparticles in porous media is of importance.…”
Section: Nanoparticle Flow Behaviour In Porous Mediamentioning
confidence: 99%
“…The agglomeration inhibits their mobility and reduces the chemical reactivity of nanoscale metal particles. Extensive studies reported the use of water-soluble starch, sodium carboxymethyl cellulose, natural organic matter, silica, and resin as a surfactant or support to prevent the agglomeration and stabilize the synthesized nanoscale metal particles [33,[37][38][39][40][41][42]. We report below some examples of the use of these iron particles for water clean-up.…”
Section: Carbon-halogen Bond Cleavage Of Hocs In Water Catalyzed By Imentioning
confidence: 99%
“…Handbook of Nanoparticles DOI 10.1007/978-3-319-13188-7_44-1 # Springer International Publishing Switzerland 2015 Trichloroethylene (TCE) Nanoparticle partition to the interface of TCE droplets, enhancing their potential for dense NAPL source zone remediation [41] Granular activated carbon 2-chlorobiphenyl Demonstrated the concept of a "reactive" capping barrier composed of carbonsupported nZVI/Pd for the remediation of polychlorinated biphenyls [42] Pillared bentonite (Al-bent)…”
Section: Synthesis Approachesmentioning
confidence: 99%